The Long-Term Recovery of Parotid Glands in Nasopharyngeal Carcinoma Treated by Intensity-Modulated Radiotherapy - Tasaka, Shun; Jingu, Keiichi; Takahashi, Noriyoshi; Umezawa, Rei; Yamamoto, Takaya; Ishikawa, Yojiro; Takeda, Kazuya; Suzuki, Yu; Kadoya, Noriyuki (Frontiers in Oncology, 2021)
Background Xerostomia is one of the most common adverse events of radiotherapy in head and neck cancer patients. There have been many reports on functional changes of the parotid gland after radiation therapy, but there have been few reports on the volume of the parotid gland and its relationship with oral quality of life (QOL) and even fewer reports on longitudinal change of the parotid gland volume. The purpose of this study was to evaluate the long-term change of the parotid gland volume after intensity-modulated radiotherapy (IMRT) for nasopharyngeal carcinoma and the relationship between parotid irradiation dose and xerostomia symptoms. Methods We retrospectively analyzed 26 patients with nasopharyngeal cancer treated by IMRT. Longitudinal changes of parotid gland volumes after IMRT were evaluated on CT images. The parotid gland volumes in each period were converted to the ratio to parotid gland volumes before radiotherapy (relative parotid volume). Dunnett’s test was used to evaluate the longitudinal changes in relative parotid volumes at 0-6, 7-18, 19-30, 31-42, 43-54 and 55-66 months after IMRT. We assessed xerostomia 3 years or more after IMRT by measuring the degree of oral moisture using a moisture-checking device (Mucus, Life Co., Ltd.) and oral QOL evaluation by GOHAI (General Oral Health Assessment Index). Results The relative parotid volumes during radiotherapy and at 0-6, 7-18, 19-30, 31-42, 43-54 and 55-66 months after IMRT were 75.2 ± 14.3%, 67.2 ± 11.4%, 68.5 ± 15.9%, 72.4 ± 14.8%, 73.0 ± 13.8%, 76.2 ± 17.5%, and 77.1% ± 17.3%, respectively. The parotid volume had recovered significantly at 43-54 and 55-66 months after IMRT, especially in parotids receiving less than 40 Gy as the mean dose. The mean irradiated dose for bilateral parotids showed negative correlations with oral QOL score and oral moisture after a long period. Conclusions The parotid volume recovered gradually but had not reached a plateau even 3 years after radiotherapy, especially in parotids receiving less than 40 Gy as the mean dose.